Automatización del proceso de evaluación del aprendizaje para el avance de la acreditación de la escuela académica profesional de ingeniería de sistemas e informática de la universidad nacional de San Martín – Tarapoto - Campojó Vásquez, Abner Purificación (2015)
The accreditation process that EAPISI is going through, looking through practical advance the process solutions, in this case we focus on a standard that is part of it, by automating the process of assessment of learning seeks to advance the accreditation of the school. By automating the process of assessing student learning of EAPISI, can do with more transparency the development and advancement of the courses, increasing the satisfaction and acceptance from students about the process, thereby achieving a significant advance over the school accreditation. The population used were students EAPISI; some of these students was sampled first pre satisfaction survey applied to students before automation and then a post survey was conducted after automate the process, the results were compared of which results were very favorable. Automating the process of assessment of learning is the creation of an information system, with which it seeks to develop the process more appropriately, based on transparency and satisfaction by students, thus achieving an important step in the accreditation process of the EAPISI. Data for hypothesis testing were obtained from the evaluation of a group of students during the 2014-II and 2015-I cycles, which showed that automate the process of learning assessment generates an advance in the accreditation of EAPISI UNSM-T.